Information structure in Isthmus Zapotec narrative and conversation - Bueno Holle, Juan José (Topics at the Grammar-Discourse Interface, 2019)
This book presents an in-depth description of information structure in Isthmus Zapotec, an Otomanguean language spoken by around 50,000 people in southeastern Oaxaca, Mexico, and represents the first book-length treatment of information structure in a Mesoamerican language. Three main observations motivate the study: Strong documentation and a relatively large and active speaker community create a unique opportunity to document information structure in Isthmus Zapotec and to study the language as it is used by speakers in everyday life; As a tonal and verb-initial language, the examination of Isthmus Zapotec represents a chance to explore the possible combinations of tone, intonation, morphology and verb-initial syntax that may occur in the coding of information structure.